Tratamento de água cinza e sua aplicação na fertirrigação do girassol ornamental em ambiente semiárido - Fernandes, Isaura Raquel Dantas (Universidade Federal Rural do Semi-Árido, 2017)
The lack of treatment of domestic effluents as well as their inadequate disposal characterizes as an environmental and public health problem, this problem was identified at the headquarters of the Associação Comunitária Reciclando para a Vida – ACREVI, located in the periurban area of the municipality of Mossoró-RN, where about 20 associates live daily producing a considerable volume of gray water and throwing it in the open without any treatment. In view of the problems presented, a low cost system for the treatment of gray water was installed in ACREVI, aiming at the use of this effluent in the ornamental sunflower fertirrigation (Sol Noturno variety), which is a species differentiated by presenting reddish petals. This research had as main objective to evaluate the efficiency of the primary treatment in domestic effluents produced in ACREVI and to investigate its effects on ornamental sunflower fertirrigation. The treatment system consists of a masonry passage pa box, a two-chamber septic tank with a capacity of 1000 L, an anaerobic filter with a capacity of 500 L and a reservoir of 500 L. The physical, chemical, biochemical and microbiological analyzes of gray water were carried out monthly for 6 months before and after treatment. The experiment with ornamental sunflower was developed in protected environment, in randomized blocks with 5 treatments and 3 replicates. The treatment fertigation nutritive solutions consisted of the dilution of gray water in municipal supply water (75, 50 and 25%) and two controls (irrigation with 100% water supply and gray water irrigation - 100%). The development of the plant was monitored every 15 days after germination by means of the evaluation of the plant height, stem diameter, leaf number and leaf area parameters. In order to evaluate the production of flowers, the following variables were verified: external diameter of the chapter, number of petals in the chapter, beginning of flowering and duration after flowering. The leaf tissue of the sunflower was also analyzed to determine the N, P, K, Ca and Mg contents of the plant. According to the analyzes performed in raw gray water and treated gray water, the treatment system proved to be efficient in removing the main pollutants. The use of gray water in ornamental sunflower fertirrigation did not interfere in the growth variables, as well as the indicators of flower production quality. The decreasing order of nutrient uptake by the sunflower leaf was Ca> N> K> Mg> P. Finally, it can be concluded that the treated gray water can be used in the crude form in the ornamental sunflower fertirrigation without causing production losses and without compromising the quality of the flowers
Gray water treatment and its application in ornamental sunflower fertigation in semiarid environment
Keywords: Ambiente protegido; Fertirrigação; Helianthus annuus; Tanque séptico; Filtro anaeróbio; Protected environment; Fertigation; Helianthus annuus; Septic tank; Anaerobic filter; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO